Good Corporate Governance dan Profitabilitas pada Praktik Income Smoothing - Antari, Ni Komang Maya; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p10, 2023)
The research aims to obtain empirical evidence regarding the effect of good corporate governance and profitability on income smoothing practices with firm size and type of industry as control variables. The research was conducted on all companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research sample consisted of 64 observations determined by purposive sampling method. The data analysis technique used is logistic regression analysis. The results showed that good corporate governance and profitability have a negative effect on income smoothing practices, and company size and type of industry as control variables have a positive effect on income smoothing practices. The theoretical implications of this study are able to support agency theory, stewardship theory, and positive accounting theory, as well as practical implications that can be taken into consideration by companies and investors in making economic decisions. Keywords: Income Smoothing; Good Corporate Governance; Profitability; Firm Size; Type of Industry